Happiness Eudaimonia Honorary Teachers Who Teach In Remote Areas (Talango Island, Sumenep) - Rahman, Syahnur; Fattah Hanurawan; Hetti Rahmawati; Immanuel Hitipeuw (Jurnal Pendidikan Anak, 2024)
Abstract In the world of education, teacher well-being and happiness play a vital role in creating an effective and positive learning environment for students. Teachers who experience a deep sense of satisfaction and fulfillment in their professional duties are more likely to be motivated, engaged, and emotionally invested in the academic growth and success of their students. This study aims to determine the welfare of honorary teachers in a remote area, namely Talango Elementary School, Sumenep. This study uses a phenomenological approach with participants study This are six honorary teachers from S ekolah Dasar Negeri 1 Talango Sumenep. Eudaimonia and teacher happiness are two important aspects that influence job satisfaction and overall well-being in the field of education. There are several factors that contribute to teacher happiness. Teacher job happiness is very important in the successful implementation of educational reform and has a significant impact on their work performance, commitment, and motivation. Teachers who are satisfied and happy in their jobs are more likely to create positive and effective learning experiences for their students. Teachers in remote areas have close relationships with their students, which is beneficial for teacher well-being. Future research can further explore empirical evidence to support the proposed relationship between teacher well-being and student well-being